Labor Force and Unemployment in the 1920's and 1930's: A Re-Examination Based on Postwar Experience - Coen, Robert M. (The Review of Economics and Statistics, 1973)
A NNUAL data on the labor force were not collected by the United States government before 1940. The decennial censuses prior to 1940 did include labor force enumerations, although the definitional basis of these figures was the concept rather than the labor force concept which underlies census data beginning in 1940.' Stanley Lebergott (1964) has undertaken the most careful and exhaustive adjustments of the gainful worker figures to make them consistent with the labor force concept and with the sampling procedures used by the Census Bureau in its Current Population Surveys which began in 1940. He has also constructed an annual labor force series for the 1900-1939 period which is consistent with his adjusted decennial census figures. One shortcoming of these annual labor force estimates is that they do not fully reflect the influence of economic variables on labor force participation. His procedure was basically to (1) obtain detailed labor force participation rates by age, sex, and in some cases, nativity, for decennial census years, (2 ) interpolate these rates linearly between census years, and (3) apply the interpolated rates to population data for the intercensoral years. As one might expect, the resulting labor force series displays virtually no cyclical variation, since annual changes in labor market conditions are not taken into account. Thus, Lebergott's annual estimates are not of the same character as the annual (or monthly) estimates prepared by the Census Bureau after 1940,2 and unemployment rates derived from them are not truly comparable with the official series for the post1940 years. Empirical studies of post-World War II data indicate that the size of the labor force in the short run depends in part on the degree of tightness in the job market.3 The search for